Further Properties of 1- and 2-Dimensional U- and W-Convexity and Fixed Point of Nonexpansive Mappings in Banach Spaces X and X∗. (4th May 2021) - Gao, Ji
Abstract : In this paper, we further studied properties of the modulus of n -dimensional U -convexity and the modulus of n -dimensional U -flatness when n = 1 (2-dimensional character) and n = 2 (3-dimensional character). The new properties of these moduli are investigated, and the relationships between these moduli and other geometric parameters of Banach spaces are studied. Some results on fixed point theory for nonexpansive mappings and normal structure in Banach spaces are obtained.